wxHaskell - A Portable and Concise GUI Library For Haskell - Leijen, Daan (ACM SIGPLAN Haskell Workshop (Haskell'04), Snowbird, Utah, 2004)
wxHaskell is a graphical user interface (GUI) library for Haskell that is built on wxWidgets: a free industrial strength GUI library for C++ that provides a common interface that has been ported to all major platforms, including Windows, Gtk, and MacOS X. In contrast with many other libraries, wxWidgets retains the native lookand-feel of each particular platform. We show how distinctive features of Haskell, like parametric polymorphism, higher-order functions, and first-class computations, can be used to present a concise and elegant monadic interface for portable GUI programs.
Snowbird, Utah